Case Report: Post-traumatic splenosis and potential pitfall for PSMA-PET - Nearchou, Marina; Georgiou, Elizabeth; Vrachimis, Alexis; Ferentinos, Konstantinos; Strouthos, Iosif (Frontiers in Nuclear Medicine, 2023)
Background 18F-prostate specific membrane antigen (PSMA) PET is fast becoming the gold-standard in prostate cancer, both in staging of intermediate-/high-risk patients and in re-staging patients with biochemical failure. Several pitfalls of 18F-PSMA PET have been reported, and we report, to our best of knowledge, for the first time, a case which could have been falsely diagnosed as peritoneal spread. Case presentation A 67-year-old patient with high-risk prostate cancer underwent staging with 18F-PSMA-1007 PET/CT (PSMA-PET/CT). PSMA-PET/CT revealed a histologically confirmed prostatic malignancy in the peripheral left zone. Unexpectedly, additional multiple highly PSMA-expressing intraabdominal formations were discovered. Based on apparent anatomic asplenia and a history of traumatic splenic rapture during childhood, a suspicion of post-traumatic splenosis was raised. For further non-invasive evaluation, a C-99 sulphur colloid scintigraphy with SPECT was conducted, confirming the presence of multiple functional ectopic splenic tissues. This is, to our best of knowledge, the first case utilising 18F-PSMA-1007-PET/CT and 99mTc-sulphur colloid SPECT to detect intraabdominal splenosis, highlighting the high potential of nuclear medicine in such trivial cases.